Effectiveness of the Kangaroo Method for Reduce Pain in Intra-Muscular Injections in Newborn Infants - Imar Khoiriah; Feva Tridiyawati (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: Causes of infant mortality from various diseases can be prevented by giving immunizations to infants from birth, but adverse reactions related to immunization are also increasing. Pain caused by injection is an acute pain that is felt by children as an unpleasant sensory and emotional experience as a result of tissue damage. One of the efforts to reduce the pain felt by neonates is to provide midwifery care, namely the kangaroo method. Knowing the effectiveness of the kangaroo method to reduce pain in intramuscular injections in newborns. Methods: Quasi experimental with Posttest Only Control Group Design. All newborns at PMB Imar khoiriah in August-October 2022 at the time of data collection were 30 people (accidental sampling). Results: The distribution of pain levels in the intervention group was mostly mild pain of 80%, and in the control group the majority of moderate pain was 73.3%. The average pain in the intervention group was 2.60 and in the control group was 4.93. There is an effectiveness of the kangaroo method to reduce pain on intramuscular injection in newborns (p value 0.000). Conclusions: There is effectiveness of the kangaroo method for reducing pain in intramuscular injections in newborns. It is hoped that midwives can use the kangaroo method as a reference for non-pharmacological pain management interventions in newborns.